2005
DOI: 10.1017/s147474640500254x
|View full text |Cite
|
Sign up to set email alerts
|

A Realistic/Theory of Change Approach to the Evaluation of Health Promotion in Small- and Medium-Sized Enterprises in Sandwell

Abstract: Discovering a theory of change for health promotion in small- and medium-sized enterprises highlights important lessons about how successful workplace health interventions work and the conditions conducive to positive outcomes for ‘hard to reach groups’. In the evaluation of targeted health promotion initiatives carried out by the Workwell project in Sandwell, a theory of change has emerged that indicates the need for a sensitive understanding of the contexts of interventions and the importance of developing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Workplace Health Promotion for SMEs is reported to directly assist in adding value for customers and employees through increased productivity, reduced absenteeism and improved morale (Carroll et al, 2005). It is the latter that emerged as being more important for the participating organisations:…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Workplace Health Promotion for SMEs is reported to directly assist in adding value for customers and employees through increased productivity, reduced absenteeism and improved morale (Carroll et al, 2005). It is the latter that emerged as being more important for the participating organisations:…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Carroll (2005) indicated that outcomes were not always measurable or quantifiable in terms of financial or health-related targets. Recording and quantifying benefits appeared to be an element of the programme participants expected the external facilitator to undertake or they were more interested in the less tangible benefits such as noted here:…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature search, covering the last decade and searching CINAHL, Embase, Medline, PsychARTICLES, PsycINFO and SocINDEX (through the EBSCO interface) for the term TBE and/or commonly used variants did reveal several UK based evaluations, with formative aims [11,26,27]. For example, adoption of a TBE approach in the evaluation of Health Action Zones in England was described as being intended to enable the evaluation to contribute to the process of learning [26].…”
Section: Introductionmentioning
confidence: 99%